2018
DOI: 10.12659/msm.908032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Appendiceal Neoplasms on 3544 Appendectomy Specimens for Acute Appendicitis: Retrospective Cohort Study of a Single Institution

Abstract: BackgroundAppendiceal neoplasms are rare and generally determined in appendectomy specimens for acute appendicitis. Depending on a tumor’s histopathology and size, appendectomy or right hemicolectomy are the surgical treatment options. Adenocarcinomas, mucinous neoplasms, goblet cell carcinoids and neuroendocrine tumors are the types of the primary appendiceal neoplasm histopathology. In this study, we aimed to determine the incidence of appendiceal neoplasms in an acute appendicitis cohort. Also, histopatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 12 publications
0
36
1
Order By: Relevance
“…Malignancy is an important, albeit rare, cause of acute appendicitis in older adults [ 10 , 11 ]. Studies have found neoplasms in up to 2.5% appendectomy specimens [ 12 , 13 ], with only about 0.1% being metastatic [ 14 , 15 ]. Neuroendocrine tumors are the most common primary appendiceal neoplasms associated with acute appendicitis [ 11 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignancy is an important, albeit rare, cause of acute appendicitis in older adults [ 10 , 11 ]. Studies have found neoplasms in up to 2.5% appendectomy specimens [ 12 , 13 ], with only about 0.1% being metastatic [ 14 , 15 ]. Neuroendocrine tumors are the most common primary appendiceal neoplasms associated with acute appendicitis [ 11 , 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found neoplasms in up to 2.5% appendectomy specimens [ 12 , 13 ], with only about 0.1% being metastatic [ 14 , 15 ]. Neuroendocrine tumors are the most common primary appendiceal neoplasms associated with acute appendicitis [ 11 , 12 , 14 ]. Other primary appendiceal neoplasms identified in the causation of acute appendicitis include adenomas (sessile serrated adenoma, tubular adenoma, and villous adenoma), adenocarcinoma, and low-grade and high-grade appendiceal mucinous neoplasms [ 11 , 12 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among appendiceal neoplasms, appendiceal adenocarcinoma portends a worse overall prognosis and represents a clinical challenge, particularly in the setting of perforated appendicitis. Patients are often diagnosed with appendiceal adenocarcinoma due to nonspecific tumor‐related symptoms, including abdominal bloating and appendicitis 3‐9 …”
Section: Introductionmentioning
confidence: 99%
“…While the current reported incidence of appendiceal adenocarcinoma in all appendectomy pathology specimens is low, ranging 0.08%–2%, the incidence of appendiceal adenocarcinoma has increased over the previous decade by 54% across all histologic subtypes, stages, and ages 3‐9 . Prior studies have shown that, among those presenting with appendicitis, appendiceal adenocarcinoma is more common among older patients, specifically those greater than 50 years of age, patients with greater comorbidities based on American Society of Anesthesiologists (ASA) classification, patients who have absence of traditional symptomatology (i.e., migratory right lower quadrant abdominal pain), and patients who present with phlegmonous findings on imaging; the sensitivity and specificity of these prognostic factors though has not been consistently reported 7‐12 …”
Section: Introductionmentioning
confidence: 99%
“…Current guidelines suggest that simple appendectomy is adequate treatment for ANETs if they are <1 cm, and right hemicolectomy is recommended for those bigger than 2 cm. However, ideal treatment of 1–2 cm tumors is still controversial [5, 6].…”
Section: Introductionmentioning
confidence: 99%